International Debt Statistics 2021 - World Bank (Washington, DC: World Bank, 2020)
International Debt Statistics (IDS) is a longstanding annual publication of the World Bank featuring external debt statistics and analysis for the 120 low- and middle-income countries that report to the World Bank Debt Reporting System (DRS). The content coverage of IDS 2021 includes: 1) a user guide describing the IDS tables and content, definitions and rationale for country and income groupings, data notes, and description of the additional resources and comprehensive datasets available to users online, 2) a brief overview analyzing global trends in debt stocks and debt flows to low- and middle-income countries within the framework of aggregate capital flows (debt and equity), 3) a feature story on the World Bank and IMF Debt Service Suspension Initiative (DSSI) in response to the Covid-19 pandemic, 4) tables and charts detailing debtor and creditor composition of debt stock and flows, terms volume and terms of new commitments, maturity structure of future debt service payments and debt burdens, measured in relation to GNI and export earnings for each country, and 5) one-page summaries per country, plus global, regional and income-group aggregates showing debt stocks and flows, relevant debt indicators and metadata for 5 years (2015-2019).